IMPLEMENTATION OF LOCAL AREA NETWORK FOR OPTIMIZATION OF DATA PROCESSING (Study at Bank of East Java Small Medium Enterprise in Surabaya) - Astherina Kristianty (Jurnal Administrasi Bisnis, 2015)
The objectives in this research are to describe implementation of LAN (Local Area Network) for optimization of data processing and To know the LAN (Local Area Network) be used optimally in data processing. The research used descriptive qualitative research approach to the analysis developed by Miles and Huberman data collection, data reduction, and conclusion. Collecting data using observation, interview employee Bank UMKM Jatim Surabaya. The results of this research are according to sources, the use of LAN in the processing of customer data is said to be optimal. However, the observation that researchers do, there are some shortcomings and problems that led to the conclusion that the use of the LAN for the processing of customer data Bank of East Java Small Medium Enterprise in Surabaya used LAN with IP and router in each computer, used of LAN is optimal, but still has some problem that occur, and the weakness is data leakage often occurs.   Keywoard: computer network, local area network, optimization, data processing.